Implementasi Sistem Manufaktur Fleksibel (FMS) dalam Menjawab Tantangan Permintaan Pasar Dinamis - Abdurrozzaq Hasibuan; Sukma Amelia Wardani; Riska Ramadhani; Rifky Rifaldi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The manufacturing industry faces the challenges of increasingly dynamic and diverse market demands. Flexible Manufacturing System (FMS) is present as a solution by offering high flexibility in the production process. Through automation and digital integration, FMS is able to accelerate product changeover time and increase operational efficiency. This study uses a literature review method to analyze the benefits and challenges of FMS implementation. As a result, FMS has proven effective in increasing the efficiency and competitiveness of companies, although it requires large investments and human resource readiness. With the right strategy, FMS is the key to industrial adaptation to market changes.